Predictors of substance use in a clinical sample of youth seeking treatment for Trauma-related mental health problems. (March 2021) - Adams, Zachary W.; Hahn, Austin M.; McCart, Michael R.; Chapman, Jason E.; Sheidow, Ashli J.; Walker, Jesse; de Arellano, Michael; Danielson, Carla Kmett
Highlights: Substance use risk factors were examined in trauma-exposed youth seeking treatment. PTSD-Avoidance and depression symptoms were associated with alcohol use. Social motives and sensation seeking were also associated with alcohol use. Coping and enhancement motives were independently associated with cannabis use. Abstract: Child maltreatment and traumatic events are well established risk factors for adolescent substance use problems, but little is known about the unique contributions of etiological factors on trauma-exposed youths' pre-treatment substance use in clinical settings. This study examined associations between substance use and risk and protective factors measured across multiple ecological levels among a unique sample of youth seeking treatment for trauma-related mental health problems in child advocacy centers. Participants were adolescents (N = 135; 85% female; 60% white, 31% black) aged 13–17 years (M = 15.4) with ≥ 1 experience of child maltreatment or other interpersonal violence, current substance use, and ≥5 PTSD symptoms. Youth and caregivers completed validated questionnaires and clinical interviews at a pre-treatment assessment in a randomized controlled trial of a treatment for co-occurring traumatic stress and substance use. Negative binomial regression models identified different patterns of risk and protective factors for alcohol and cannabis. Clinical implications of these results are discussed, including the potential targets for integrated psychotherapies that address co-occurring substance use and traumatic stress in youth.